Processes of change in academia – the impact of government and market - Rosicki, Remigiusz (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
The paper describes the problems associated with the development of universities and higher education on a global scale and based on the example of Poland. To illustrate the subject, the research focuses on: (1) the idea of university autonomy and elitism from a historical and contemporary perspective, (2) the delusion of elitism and social advancement of education which is attributed to it, (3) the myth of flexibility of education generated among others by politicians. The text indicates the main processes in academia: (1) centuries long removal of the autonomy of universities, (2) the ‘humanistic ethos’ of universities is also removed, (3) universities are transformed into ‘vocational colleges’, (4) higher education is developed as one of the service sectors, (5) universities are transformed into institutions responsible for the labour market, (6) universities are entered in the ‘logic of the free market’, (7), the number of the educated is increasing, (8) the fetishisation of education, (9) the myth of flexibility of education and the its multifunctionality in the context of limited absorption capacity of the labour.

W tekście podjęto problematykę związaną z rozwojem uniwersytetów i szkolnictwa wyższego w wymiarze globalnym i na przykładzie Polski. Dla zobrazowania podjętego problemu skupiono się na: (1) idei autonomii i elitaryzmu uczelni w perspektywie historycznej i współczesnej, (2) ułudzie elitaryzmu wykształcenia i awansu społecznego jaki się jemu przypisuje, (3) micie elastyczności wykształcenia generowanego m.in. przez polityków. W tekście wskazano na główne procesy zachodzące w nauce: (1) z wiekami następowało znoszenie autonomii uniwersytetów, (2) usuwany jest „humanistyczny etos” uniwersytetów, (3) uniwersytety przekształcane są w „wyższe szkoły zawodowe”, (4) szkolnictwo wyższe rozwijane jest jako jeden z sektorów usług, (5) uniwersytety przekształcane są w instytucje odpowiedzialne za rynek pracy, (6) uniwersytety wpisywane są w „logikę działania wolnego rynku”, (7) wzrasta liczba wykształconych, (8) następuje fetyszyzacja wykształcenia, (9) podtrzymywany jest mit elastyczności wykształcenia i wielokierunkowości w kontekście ograniczonej chłonności rynku pracy, (10) rozwijane są systemy odpłatności za studia w szkolnictwie publicznym.
Procesy zmian w nauce – wpływ władzy i rynku
Keywords: fetishization of education; development of science; higher education; market; reproduction of labour force; fetyszyzacja edukacji; rozwój nauki; szkolnictwo wyższe; rynek; reprodukcja siły roboczej